Exploring Discrepancies in the Utilization of Joint Marital Assets: A Normative-Sociological Analysis - Umar, Fazlon; Kurniawan, Cecep Soleh (Journal of Mujaddid Nusantara, 2024)
Joint assets in marriage encompass all assets acquired after marital status is established through a legal union and are jointly owned by both spouses or held in joint names acquired simultaneously during marriage. Indonesian Positive Law, including Law no. 16 of 2019 concerning Marriage, the Compilation of Islamic Law, and the Civil Code (KUHP), governs the utilization of joint property in marriage, ensuring equal rights for both parties. However, discrepancies exist between legal provisions and public understanding regarding the use of joint marital assets. This study, conducted in Trienggadeng Pidie Jaya, employs qualitative methods to explore the community's comprehension of joint property using Indonesian Positive Law as an analytical framework. It adopts a normative-sociological approach, treating Indonesian Positive Law as the basis for analyzing societal perceptions and behaviors related to collective property. The research reveals discrepancies between normative rules and public understanding of the regulations governing the use of joint marital assets.